2023
DOI: 10.1021/acs.inorgchem.3c00504
|View full text |Cite
|
Sign up to set email alerts
|

Oxido-Molybdenum(V) Corroles as Robust Catalysts for Oxidative Bromination and Selective Epoxidation Reactions in Aqueous Media under Mild Conditions

Abstract: Two new meso-substituted oxido-molybdenum corroles were synthesized and characterized by various spectroscopic techniques. In the thermogram, MoO[TTC] (1) exhibited excellent thermal stability up to 491 °C while MoO[TNPC] (2) exhibited good stability up to 318 °C. The oxidation states of the molybdenum(V) were verified by electron paramagnetic resonance (EPR) spectroscopy and exhibited an axial compression with d xy 1 configuration. Oxido-molybdenum(V) complexes were utilized for the selective epoxidation of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 69 publications
0
17
0
Order By: Relevance
“…Mo-1 exhibits bathochromic shift of 8-9 nm in B and Q bands relative to meso-functionalized oxido-Mo corroles. [60,63] Mo-2 exhibits bathochromic shift in the most intense B (Δλ max = 26 nm) as well as Q band (Δλ max = 33 nm) relative to Mo-1 as seen in Figure 1. Also, Mo-2 exhibits bands at 324 and 398 nm, most likely due to the attachment of the strong chromophore-like DCV on the macrocycle.…”
Section: Photophysical and Ft-ir Studiesmentioning
confidence: 93%
See 2 more Smart Citations
“…Mo-1 exhibits bathochromic shift of 8-9 nm in B and Q bands relative to meso-functionalized oxido-Mo corroles. [60,63] Mo-2 exhibits bathochromic shift in the most intense B (Δλ max = 26 nm) as well as Q band (Δλ max = 33 nm) relative to Mo-1 as seen in Figure 1. Also, Mo-2 exhibits bands at 324 and 398 nm, most likely due to the attachment of the strong chromophore-like DCV on the macrocycle.…”
Section: Photophysical and Ft-ir Studiesmentioning
confidence: 93%
“…[51][52][53][54] It has been observed that KBr with H 2 O 2 facilitates oxidative bromination reactions many folds. [55][56][57][58][59] Reports on molybdenum corroles have shown their utility in catalysis is scarce for brominating phenols, [60] hydrogen evolution, [61,62] and epoxidation of alkenes. [63] Brominated phenols are widely investigated using 3d transition metal complexes due to their utility in pharmaceutical industries for biological applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from their sensitive electronic configuration, corroles exhibit very high structural diversity, unique coordination chemistry, and strong light absorption/emission properties in comparison to porphyrins. A judiciously selected functionalization of the corrole ring’s periphery can change not only the molecule’s electronic properties, redox potentials, and coordination chemistry , but also lead to new possibilities in the areas of nonlinear optics, , near-infrared phosphorescence, catalysis, and fluorescence. , In addition to these areas of research, corrole macrocycles are good prospects for a range of sensing material applications due to their distinctive optical characteristics and synthetic adaptability. , In fact, the unusual behavior, reactivity, and high acidity of corrole imino protons have been utilized for the sensing of basic anions like CN – , F – , OAc – , and H 2 PO 4 – ions through an anion-induced deprotonation mechanism . Lodeiro and co-workers have investigated several gallium­(III) corroles for sensing toxic cyanide and fluoride anions, , while Gros and co-workers developed cobalt corrole-based porous organic polymers (POPs) for selective CO adsorption .…”
Section: Introductionmentioning
confidence: 99%
“…In the last few decades, molybdenum has been employed in the synthesis of new bioinspired complexes coordinated by different ligands with biological importance like amino acids and carbohydrates. 1 These new molybdenum( vi ) complexes have been evaluated for their catalytic activity for reactions with industrial and biological significance like oxidation of alcohols, oxidative halogenations of organic substrates, 2 as well as extensively applied in oxygen atom transfer (OAT) processes, such as epoxidation reactions 3–9 and sulfide oxidations. 10–15 Industrially, molybdenum-based materials and complexes are widely applied in plenty of oxidation reactions, hydrocarbon dehydrogenations, polymerization reactions and alkene metatheses.…”
Section: Introductionmentioning
confidence: 99%